Getting it right advanced skills for auditors - Campbell, Catherine; Nicholas & Smith Pty Ltd (Sydney : Nicholas and Smith, 1996)
The video gives auditors the chance to take a front row seat in a typical audit in a real work environment. Auditors will see how the right techniques and questioning skills can be used to deal with range of staff and situations
Copy available in DVD format
Presenter: Chris Costello, Noel, Jon-Claire-Lee
Keywords: Audit committees; Auditors